TEOLOGI SUFI KAJIAN ATAS MISTISISME CINTA JALALUDDIN RUMI - Miftahul Jannah (JURNAL AL-AQIDAH, 2020)
This paper will examine the idea of mycticisme love carried by Jalaluddin Rumi. In his journey as a Sufi, Rumi managed to take his own Sufism form and give a new nuance that was considered different from most Sufis of his time. Sufism thinking contained in the form of poetry and poetry known as the path of love (mystic love). This paper is a reseach library using descriptive analysis method to study the thoughts of Divine love Jalaluddin Rumi. The love carried by Rumi signals to live in harmony with the principles of peace and tolerance. Poetry becomes one of the most appropriate means to express the inner state he feels. With the idea of divine love he introduced, Rumi was able to pour all kinds of feelings and expressions of his personal religious experience into deeply poetic verses. Poems born of a heart yearning for union with the Beloved, until when the Beloved Being is the only being that exists. Love, which is the light of life and human values, is actually eternal. So it must be for the eternal. He does not deserve to be given to those who are destined to be mortal and perish.